Improvement Of The Method Of Heat Calculation Of The Drum Dryer For Cotton-Raw - A.K.Usmankulov, F.S.Sadikov, U.A.Norboev, B.T.Abbazov (International Journal of Advanced Science and Technology, 2020)
This article is devoted to the development of scientifically based methods for calculating the heat transfer coefficient taking into account the physicomechanical and other indicators of raw cotton and the design parameters of the drying drum device. The method of thermal calculation of a drum dryer, taking into account the degree of flowability of raw cotton, has been developed. The thermal calculation of drum dryers is based on the graphoanalytical method for determining the parameters characterizing the heat transfer condition in the drying chamber used in the calculation of drum dryers for bulk materials. It has been studied that the amount of heat perceived by raw cotton mainly depends on the total surface of particles falling from the blades. A rational value of the parameter necessary for efficient drying and drying drum performance was proposed, depending on the shape and size of the dryer’s internal devices. The efficiency coefficient of the blade devices is proposed, which allows determining the actual surface of raw cotton involved in heat and mass transfer with air, characterizing the efficiency of the drum’s internal devices. The free surface area of ​​the raw cotton located in the blockage and on the surface of the blades is established. The largest and smallest blade values ​​were determined. The dependencies between the parameters characterizing the heat transfer conditions, the distribution of raw cotton over the volume of the drum from the internal blade devices, and the performance that determine the heat of the transmitted raw cotton in the suspended state of the drum are obtained. The possibilities of controlling heat transfer to the raw cotton have been determined, the availability of a reserve for increasing the drying intensity by increasing the surface of the raw cotton has been experimentally established. The relationship between the design parameters of the internal devices and the productivity of the geometric shape dryer and blade sizes has been experimentally established.